Hubungan Body Image dan Kecukupan Gizi dengan Kurang Energi Kronik pada Calon Pengantin Wanita di Kecamatan Cibiru - Abellinda Putri Pribadi; Syifa F. Syihab; Isti Kumalasari; Hurry Mega Insani (Universitas Airlangga, 2025)
Background: Chronic Energy Deficiency (CED) is a significant nutritional issue affecting women of reproductive age, including future brides. This condition can have negative effects on reproductive health and the well-being of future descent. CED often arises from insufficient nutrient intake and negative perceptions of body image, which can result in unhealthy eating behaviors. In Bandung City, the Cibiru District has the highest prevalence of malnutrition among future brides. Objectives: This study aimed to analyze the relationship between body image perception and nutrient adequacy (energy, protein, fat, and carbohydrate) with the incidence of chronic energy deficiency among future brides. Methods: This study used a cross-sectional design and involved 41 respondents who were recruited through consecutive sampling. Data collection included Measuring Mid-Upper Arm Circumference (MUAC), conducting 2x24-hour food recall interviews, and administering the MBSRQ-AS. The dataset was examined using both univariate and bivariate analyses, with Pearson’s and Spearman’s correlation tests employed to assess relationships. Results: Among the respondents, 29.3% were identified as experiencing chronic energy deficiency, while over half reported a positive body image. However, most respondents did not meet the recommended intake levels for energy and macronutrients. Of all the variables assessed, only adequate fat intake was significantly related to chronic energy deficiency in future brides (p=0.029; r=0.341). Conclusion: Adequate fat intake is weakly positively related to chronic energy deficiency among future brides. No significant associations were observed between chronic energy deficiency and body image perception or the adequacy of energy, protein, and carbohydrate intake. Therefore, future brides are recommended to meet their nutritional needs, especially fat intake from healthy sources such as mackerel, skipjack tuna, sardines, avocado, and peanuts, to prevent the occurrence of Chronic Energy Deficiency (CED).